2010
DOI: 10.1371/journal.pone.0012164
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic and Probiotic Fortified Milk in Prevention of Morbidities among Children: Community-Based, Randomized, Double-Blind, Controlled Trial

Abstract: BackgroundRecent reviews suggest common infectious diseases continue to be a major cause of death among preschool children in developing countries. Identification of feasible strategies to combat this disease burden is an important public health need. We evaluated the efficacy of adding prebiotic oligosaccharide and probiotic Bifidobacterium lactis HN019 to milk, in preventing diarrhea, respiratory infections and severe illnesses, in children aged 1–4 years as part of a four group study design, running two stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 42 publications
(46 reference statements)
3
66
0
11
Order By: Relevance
“…Consequently, this period of the infant's life represents a unique window of opportunity during which time the gut microbiota may be modified with implications for health outcomes (56). A myriad of factors that affect this composition have been investigated and include mode of delivery (56), feeding choice (i.e., breast versus formula feeding) (8,45), prematurity (63,72), and the administration of probiotics (11,15,55,60) and prebiotics (10,31,65). It is also thought that exposure to antibiotics can have a significant negative influence on the composition and development of the gut microbiota in early life (7,23,35).…”
mentioning
confidence: 99%
“…Consequently, this period of the infant's life represents a unique window of opportunity during which time the gut microbiota may be modified with implications for health outcomes (56). A myriad of factors that affect this composition have been investigated and include mode of delivery (56), feeding choice (i.e., breast versus formula feeding) (8,45), prematurity (63,72), and the administration of probiotics (11,15,55,60) and prebiotics (10,31,65). It is also thought that exposure to antibiotics can have a significant negative influence on the composition and development of the gut microbiota in early life (7,23,35).…”
mentioning
confidence: 99%
“…Another study from urban India reported protection against dysentery (defined by a parental history of bloody diarrhea), although no impact was seen on the overall incidence of diarrhea [40].…”
Section: Probiotics For Bacterial Diarrheamentioning
confidence: 99%
“…Em um ECR de base comunitária, crianças de 1-3 anos de idade foram distribuídas aleatoriamente em dois grupos que receberam ou um leite utilizado como controle (n = 312) ou o mesmo leite fortificado com 2,4 g/dia de oligossacarídeos prebióticos e 1,9x10 7 unidades formadoras de colônias/dia de B. lactis HN019 (n = 312) 62 . Foi realizada vigilância doméstica duas vezes por semana para obter informações sobre o cumprimento do plano do ensaio e sobre morbidade.…”
Section: Prevenção Com Pre E Probióticosunclassified
“…A incidên-cia de episódios de disenteria foi reduzida em 21% (IC95% 0-38%, p = 0,05), enquanto a incidência de pneumonia e de infecção respiratória aguda baixa grave foi reduzida em 24 (IC95% 0-42%, p = 0,05) e 35% (IC95% 0-58%, p = 0,05), respectivamente. Comparadas às crianças do grupo controle, as crianças do grupo intervenção apresentaram uma redução de 16 (IC95% 5-26%, p = 0,004) e 5% (IC95% 0-10%, p = 0,05) no número de dias com doença grave e febre alta, respectivamente 62 . Os autores concluíram que o leite pode ser um bom meio de administração de pre e probióticos 62 .…”
Section: Prevenção Com Pre E Probióticosunclassified
See 1 more Smart Citation